가우스 곡률
Pythagoras0 (토론 | 기여)님의 2015년 2월 24일 (화) 15:33 판
개요
- \(F=0\) 인 경우\[K = -\frac{1}{2\sqrt{EG}}\left(\frac{\partial}{\partial u}\frac{G_u}{\sqrt{EG}} + \frac{\partial}{\partial v}\frac{E_v}{\sqrt{EG}}\right)\]
크리스토펠 기호를 이용한 표현
\[K = -\frac{1}{E} \left( \frac{\partial}{\partial u}\Gamma_{12}^2 - \frac{\partial}{\partial v}\Gamma_{11}^2 + \Gamma_{12}^1\Gamma_{11}^2 - \Gamma_{11}^1\Gamma_{12}^2 + \Gamma_{12}^2\Gamma_{12}^2 - \Gamma_{11}^2\Gamma_{22}^2\right)\]
역사
메모
- Math Overflow http://mathoverflow.net/search?q=
관련된 항목들